Impact of Gender & Linguistic Competence on Consecutive Interpretation - Mubarak, Ahmed Jarwan Salem et al. (University of Science and Technology, Sana'a, Faculty of Humanities and Social Sciences, Translation Program, 2024)
This study aimed to investigate the impact of gender and linguistic competence on consecutive interpretation performance. It was analytical and experimental, particularly quasi-experimental research in which a consecutive interpretation test was given to two groups of 4th level students in the Department of English and Translation at the University of Science and Technology, Hodeidah. The first group consisted of 8 male students and the other group consisted of 8 female students. The test was made up of two short videos; the first one was about a person talking about his interpreting experience and the other was about a moral story. The students' consecutive interpretation performance was evaluated out of 20 marks depending on their accuracy, fluency and confidence in interpreting. In addition, to identify the nature of the difficulties faced by the students in the interpreting process of these two videos from English into Arabic, a questionnaire of twelve reasons of difficulties was given to them. To investigate the influence of linguistic competence on the students' consecutive interpretation performance, a descriptive analysis of the students' marks in linguistic subjects during their undergraduate study was provided and analyzed. Based on a comparative, qualitative and quantitative analysis, we concluded that there was no significant difference related to gender or linguistic competence affecting consecutive interpretation performance.